Упростите выражение:

0 голосов
38 просмотров

Упростите выражение:


image

Алгебра (136 баллов) | 38 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

\frac{( \sqrt[4]{a ^{3} }+ \sqrt[4]{b ^{3} })( \sqrt[4]{a ^{3} }- \sqrt[4]{b ^{3} }) }{ \sqrt{a}- \sqrt{b} }- \sqrt{ab}= \\ =\frac{(( \sqrt[4]{a ^{3} }) ^{2} -( \sqrt[4]{b ^{3} }) ^{2} )}{ \sqrt{a}- \sqrt{b} }- \sqrt{ab}=
=\frac{ \sqrt{a ^{3} } - \sqrt{b ^{3} } }{ \sqrt{a}- \sqrt{b} }- \sqrt{ab}= \\= \frac{(\sqrt{a} - \sqrt{b})(a+ \sqrt{a} \cdot \sqrt{b} +b) }{ \sqrt{a}- \sqrt{b} }- \sqrt{ab}= \\ =a+ \sqrt{a} \cdot \sqrt{b} +b-\sqrt{ab}= a+b
(414k баллов)